2018
DOI: 10.1371/journal.pone.0190947
|View full text |Cite
|
Sign up to set email alerts
|

Field effectiveness of highly pathogenic avian influenza H5N1 vaccination in commercial layers in Indonesia

Abstract: Although vaccination of poultry for control of highly pathogenic avian influenza virus (HPAIV) H5N1 has been practiced during the last decade in several countries, its effectiveness under field conditions remains largely unquantified. Effective HPAI vaccination is however essential in preventing incursions, silent infections and generation of new H5N1 antigenic variants. The objective of this study was to asses the level and duration of vaccine induced immunity in commercial layers in Indonesia. Titres of H5N1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 42 publications
(73 reference statements)
0
25
0
Order By: Relevance
“…This is making it hard to select of a representative and genetically stable prepandemic candidate vaccine strain. Additionally, effective vaccination of animals against IAV can be influenced by several factors including, but not limited to, on-farm biosecurity measures [ 271 , 272 ], immune response of different bird species [ 272 ], immunosuppression, uncontrolled distribution and storage of the vaccines, and interference of maternal immunity with early vaccination of the offspring [ 273 ]. Rearing habits can also complicate the situation.…”
Section: Control and Prevention Of Iavmentioning
confidence: 99%
“…This is making it hard to select of a representative and genetically stable prepandemic candidate vaccine strain. Additionally, effective vaccination of animals against IAV can be influenced by several factors including, but not limited to, on-farm biosecurity measures [ 271 , 272 ], immune response of different bird species [ 272 ], immunosuppression, uncontrolled distribution and storage of the vaccines, and interference of maternal immunity with early vaccination of the offspring [ 273 ]. Rearing habits can also complicate the situation.…”
Section: Control and Prevention Of Iavmentioning
confidence: 99%
“…Despite this campaign, outbreaks of HPAI H7N9 in poultry are ongoing [ 155 ], and the potential for future outbreaks and zoonotic infections remains. Importantly, vaccination of poultry does not typically confer sterilizing immunity, and most avian influenza vaccines reduced clinical illness and spread but do not block infection or viral replication in birds [ 156 , 157 ]. As a result, vaccination may drive antigenic drift of the virus as observed Marek’s disease [ 158 ], and this may result in the reemergence of the H7N9 viruses.…”
Section: Molecular Changes and The Potential For Airborne Transmismentioning
confidence: 99%
“…These results are consistent with findings of Tarigan et al who reported that outcomes of field H5N1 vaccination were highly variable and farm-related. Specifically, HI titers of individual birds in each flock differed from those of birds in other flocks [30]. Second, GMTs varied on the farm level (Fig.…”
Section: Discussionmentioning
confidence: 98%